Global research funding for traditional, complementary and integrative medicine. - Steel, Amie; Baker, Kirsten; Adams, Jon; Foley, Hope; Carter, Tristan; Charnaud, Sarah; De Almeida, Gustavo Martin Rossell; Doo-Kingue, Philippe; Dua, Pradeep Kumar; Godatwar, Pawankumar Ramesh; Han, Eunkyung; Hill, Geraldine; et al. (Bulletin of the World Health Organization, 2025)
Objective To explore the global research funding landscape for traditional, complementary and integrative medicine. Methods We conducted a three-part study to assess the global research funding landscape. First, we searched the Dimensions database and online sources using Microsoft Copilot and Google between 12 November 2024 and 22 January 2025 for relevant grants. Second, we analysed national research infrastructure using World Health Organization (WHO) data, verified by regional contacts (14 January-28 February 2025). Third, we appraised selected funders across WHO regions, evaluating funding schemes for innovation, capacity-building and alignment with traditional medicine paradigms. Findings We identified 39 927 grants in the Dimensions database, with funding data available for 27 019 grants totalling 24.5 billion United States dollars (US$) for the years 1960 to 2024. Most grants (42.6%; 11 548) were valued under US$ 100 000, and half had a duration of 2-4 years. Cancer and cardiovascular diseases accounted for over half (8385/15 273) of topic-categorized grants, receiving US$ 5.8 billion and US$ 2.2 billion, respectively. Funders were concentrated in the Region of the Americas, and European and Western Pacific Regions. Only seven countries had schemes explicitly funding research for traditional, complementary and integrative medicine. Case study analysis of 40 schemes across 12 countries revealed limited support for traditional medicine paradigms, with few schemes meeting criteria for innovation, capacity-building or sensitivity to traditional knowledge systems. Conclusion Funding for traditional medicine research remains disproportionately low relative to its global use. Strengthening support from research funding agencies is essential to achieving the goals of the WHO Global traditional medicine strategy 2025-2034.